The Status of Empty Heads in Free Relatives in LSA - Shaheen , Buthaina (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper examines the structure of free relative clauses in Lattakian Syrian Arabic, in particular the status of the head. It will be shown that the structure of headless relatives is similar to that of headed relatives in this language in that the head is present syntactically in both (but phonologically empty in the former and overt in the latter). The empty head is identified with pro that carries the same features as the complementizer and the resumptive inside the FRC.